Konsep Ketuhanan Menurut Islam Dalam Perspektif Tauhid Dan Penerapan Dalam Kehidupan Sehari-hari - Ghozali, Imam; Tri Kurnia, Anies; Nurifatul Khoiriyah, Siti; Dwi Agustina, Rista; Nur Anisa, Khoirin; Satria Perdana, Bimo (UNIVERSITAS SERAMBI MEKKAH, 2025)
The concept of divinity in Islam is a fundamental and crucial teaching, so that it becomes the basis of Muslim beliefs. The concept of divinity in Islam is closely related to the teaching of Tawhid, which is the main basis for understanding the relationship between humanity and God. This article thoroughly discusses the concept of divinity in Islam, which includes tawhid as the main foundation, the attributes of God listed in the Qur'an, and the application of the teachings of tawhid in everyday life. Tawheed itself is divided into three main categories, namely tawheed rububiyyah (the oneness of Allah in the creation and regulation of nature), tawheed uluhiyyah (the oneness of Allah in worship), and tawheed asma wa sifat (belief in the noble attributes of Allah). In addition, the concept of divinity also includes moral aspects that guide Muslims to apply divine values in social relations and worship. Thus, a deep understanding of divinity will encourage Muslims to live better, have noble character, and always get closer to Allah SWT. The writing of this article aims to provide insight into the importance of the concept of divinity in the life of a Muslim and how this teaching can be practically applied in everyday life.